Light Strands in Slit Diffraction: Confirmatory Visualization in Media Free Environment - Dutt, Srin (European Journal of Applied Sciences, 2023)
The classic double slit experiment revealed fringe patterns thought to only result from wave interference. However, recent experiments revealed light stratifying into strands not waves after diffraction that can be directly visualized utilizing a water vapor cloud chamber. As vapor media particles may have interacted with light, this experiment was designed to avoid interference by utilizing a moving screen with extended photo exposure. Discrete, linear light strands were visualized after diffraction directly creating the pseudo-interference fringe pattern. Focal obstructions and hollow tubes did not demonstrate downstream reverberations. These results further support the particle theory of light and question wave concepts.